Development and Sustainability: A Current Discussion in the Tourist Sector - Sánchez-Rodríguez, Giovanni (2021)
This article presents a critical analysis in relation to the emergence and boom of the concepts of development and sustainability, and with the search for their assurance in companies in the tourism field, through the creation of environmental certifications. These certification saim at increasing their levels of competitiveness by outlining a path towards the paradigm of sustainability in a performativity way that postpones the understanding of the power and scope of the concept of sustainable development. The document makes a journey through different positions and perspectives of analysis of sustainable development, starting from the contributions made by the Alternative School of Development and recognizing the way in which these perspectives have been questioned and enriched by emerging paradigms that challenge the hegemonic ways of understanding this problematic. The methodology used was the search, the classification and the analysis of secondary information contained in specialized databases, such as Scopus and Web of Science. In addition, the consultation of documents produced by international organizations involved in the analysis topics. This approach allowed us to identify a renewed discussion in relation to the role of business organizations in the search for sustainable development. It also reveals the danger of sticking to functionalist perspectives that favor inappropriate and simplistic uses of complex concepts.